Clinical dilemma of DKA and Covid-19 infection: A case report - Gianniosis, Margarita (IDCases, 2020)
A 52-year-old man with no significant past medical history was found to have diabetic ketoacidosis (DKA) in the setting of COVID-19 infection. He presented with hyperglycemia and an anion gap metabolic acidosis, but without a clear infectious precipitant. Inflammatory markers were subsequently checked, and found to be significantly elevated, raising the suspicion for COVID-19 as a possible etiology despite the lack of typical symptoms - a rapid COVID-19 PCR test checked afterwards was found to be positive. The patient’s hospital course was uncomplicated, but the case highlights the possibility of COVID-19 serving as an infectious precipitant for DKA, even when a patient is otherwise asymptomatic in terms of having COVID-19.